Are the rhizosphere fungal communities of Nothofagus alpina established in two different environments influenced by plant genetic diversity? - Fernandez, Natalia Veronica (2020)
Fungi are one of the most important soil microorganisms due to their abundance and the importance of the ecosystem processes they carry out, like decomposition, nutrient cycling, and the establishment of biological interactions such as mycorrhizas. Fungi can be used as bioindicators because they are highly sensitive to alterations in their surroundings, thus being useful for monitoring ecological changes and effects of human activity on natural ecosystems. Nothofagus alpina (raulí) is an ecologically and economically important species of South American temperate forests. It is currently included in domestication and conservation programs, and provenance trials have been installed in different ecosystems of Patagonia. These trials are ideal for studying how tree genetics might influence the associated microbiota. Afforestation with fast-growing exotic conifers (mainly Pinus ponderosa) had been promoted as an important economic activity in Patagonia, but nowadays there is an increasing interest for the establishment of mix Pinus + Nothofagus plantations instead of monospecific Pinus stands and for using Pinus plantations as refugee for assisted Nothofagus migration. The main objective of this work was to explore the structure of different fungal communities in the rhizosphere of N. alpina with different genetic diversity (high, intermediate, and low) implanted under a native Nothofagus forest and a P. ponderosa plantation. Fingerprinting based on Temperature Gradient Gel Electrophoresis revealed differences in the structure of the rhizosphere fungal communities. Some relationships between N. alpina genetic diversity and composition of rhizosphere fungal communities were observed. In the native forest, one of the provenances (intermediate genetic diversity) was associated with the highest richness of Basidiomycetes and total fungi. In addition, individual genetic parameters of N. alpina specimens implanted in the native forest significantly correlated with Ascomycetes richness. It was also found that Basidiomycetes were the dominating fungal taxa in the native forest, and Ascomycetes in the P. ponderosa plantation. Factors as soil physicochemical characteristics and the dominant forestry species, which provide different quantity and quality of litter inputs and are associated with different ectomycorrhizal fungi, seemed to be the main factors determining this significant difference between the native forest and the plantation. Beyond highlighting the potential of applying soil fungi as bioindicators, our study contributes to understanding the relationship between host genetics and rhizosphere fungi. This information is relevant not only for conservation and restoration programs, but also for taking management decisions related with sustainable forestry and domestication of native tree species.